Near infrared intersubband absorption and photovoltaic detection in GaN/AIN multi quantum well structures - Baumann, Esther (My University, 2007)
Due to the large conduction band offset of nearly 2 eV between GaN and AlN, group III nitride semiconductor heterostructures are of great interest for optoelectronics based on intersubband transitions (ISBTs). These properties allow the extension of the ISBT wavelength range into the near infrared. In this work near infrared ISBTs in GaN/AlN heterostructures were investigated for samples grown by both plasma assisted molecular beam epitaxy (PAMBE) and metal-organic vapor-phase epitaxy (MOVPE). It was shown in the experiment that a 15 Å thick quantum well (QW) absorbs light around 800 meV (1.5 μm). The highest ISB absorption energy for PAMBE samples in this work is 890 meV (1.39 μm) and 834meV (1.49 μm) for MOVPE. Those results show that both growth techniques are appropriate to achieve short ISBT wavelengths. As group III nitrides are non-centrosymmetric, strong piezo- and pyro-electric fields occur in GaN/AlN heterostructures; they lead to intrinsic asymmetries in the electronic potential of a multi quantum well (MQW) structure and give rise to nonlinear optical phenomena. Based on the photoinduced polarization detection mechanism, ISB detectors were designed and investigated. Photovoltaic responses, which originate both from linear absorption as well as from step two-photon absorption were measured. These prototype photoinduced polarization photodetectors work up to room temperature. The frequency response obtained with a modulated telecommunication laser diode showed a signal up to 3 GHz. A narrow-band electro-optic modulator prototype working around 1.5 μm based on the depletion of a GaN/AlN MQW region is also presented. Those results on modulation and fast photovoltaic detection at 1.55 μm illustrate the application potential of group III nitride ISB devices as electro-optic detectors and modulators for long-haul optical fiber telecommunication
Thèse de doctorat : Université de Neuchâtel, 2007 ; Th.1956
Keywords: Hétérostructures semiconductrices; Transitions intersousbandes; Infrarouge proche; Nitrures d'élément III; Polarisation photoinduite; Semiconductor heterostructures; Intersubband transitions; Near infrared; Group III nitrides; Photoinduced polarization